The mobility of endosulfan and chlorpyrifos in the soils of the Hex River Valley - McGregor, Fiona (Department of Environmental and Geographical Science, 2024)
The Department of Community Health, University of Cape Town is assessing the quality of water supplies in the rural Western Cape, South Africa, with respect to agrochemical pollutants. This study focuses on the area of the Hex River Valley where pesticides have been detected in water samples. The two pesticides, endosulfan and chlorpyrifos, were selected for the study based on their usage and toxicity. As an initial assessment a simple screening model was used to confirm that their potential to leach into groundwater, in the Hex River Valley, is low but that their potential loss attached to sediment in runoff is high. The aim of the study was to examine the mobility of these two pesticides in the soil environment. Two soils, representative of the soils in the Hex River Valley, were sampled in August 1998. A range of chemical analyses was performed on the samples including pesticide sorption experiments in which gas chromatography coupled with electron capture detection and flame photometric detection were employed. The Hex River Valley is a sensitive area because of the intensive agricultural activities and high vulnerability of the shallow aquifer. The valley has a semi-arid climate and receives winter rainfall which averages between 240 and 329 mm per annum. The dominant soil type is sandy with a low clay and low organic carbon content. The clay fraction is dominated by mica and to a lesser extent, kaolinite as determined by X-ray diffractometry. The slightly acidic nature of the soils will retard the rate of degradation of endosulfan and chlorpyrifos and therefore endosulfan and chlorpyrifos will be more persistent than in alkaline conditions. However, the possible catalysis of hydrolysis by chelation to Fe, AI and Cu could counteract this persistence. The phosphate sorption capacity of the sandy Hex River soils (Kf = 15.8 Llkg) was compared with a clayey Shortlands soil (Kf = 620.6 Llkg) as an indicator of the potential risk associated with a particular soil for contamination of water bodies by hydrophobic insecticides. The Hex River Valley soils are considered high-risk soils because of the low sorption capacity and mobility of phosphate. The sorption coefficients of endosulfan and chlorpyrifos with the Hex River Valley soils were determined. Endosulfan was more strongly sorbed than chlorpyrifos although both endosulfan and chlorpyrifos are non-ionic, hydrophobic insecticides. However, organochlorine pesticides (e.g. endosulfan) are more persistent than organophosphates (e.g. chlropyrifos) by design. Chlorpyrifos, as anticipated, was less strongly sorbed to the University of Cape Town should be determined experimentally for site specific cases. However, this depends on the use of the output and the needs of the user. In general, GLEAMS underestimates pesticide mobility and this has been attributed to its inability to simulate: increased solubility of pesticides due to dissolved organic matter; loss of pesticides attached to suspended sediment in percolation water; pesticide and water loss via macropores; non-equilibrium sorption kinetics; and the effects of temperature and soil water content on degradation. Inaccurate curve number estimation and therefore inaccurate runoff losses, amongst other factors, are also responsible for the underestimating of runoff losses. Overall, GLEAMS estimated that endosulfan and chlorpyrifos are highly immobile in the soil environment of the Hex River Valley. However, these pesticides are being mobilised and lost from the sites of application as they have been detected in water samples taken from certain points in the valley. The major method of transport will probably be through attachment to suspended soil material (mainly organic matter) and therefore, in order to minimise the movement of these pesticides we need to minimise losses of soil material by avoiding practices liable to cause soil instability or erosion. Spray drift during application is also a potentially significant mode of transport. Large peaks of pesticide loss are unusual and may be attributable to a single event; for example, a heavy, downpour only once a year is enough to account for the entire year's pesticide loss. A field , other than the average field used for simulations in the present studies, with a steeper slope, less cover, different management practice and lower infiltration rate could also be account for the appearance of pesticides in runoff water samples. It is recommended in future studies with GLEAMS that a worst case scenario simulation be compared to an average case scenario for the Hex River Valley, in order to meaningfully describe a range of possibilities which may provide a better explanation for actual measurements of pesticide concentration in the Hex River Valley environment. The integration of GLEAMS with GIS is also suggested for future studies. The farmer is the first line of defence against pollution and it is the responsibility of government departments and pesticide manufacturers to ensure that the farmer is informed on the risk status of the area and the relevant techniques one can use to prevent pesticide contamination of the environme